12m-15=-3

Simple and best practice solution for 12m-15=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12m-15=-3 equation:


Simplifying
12m + -15 = -3

Reorder the terms:
-15 + 12m = -3

Solving
-15 + 12m = -3

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 12m = -3 + 15

Combine like terms: -15 + 15 = 0
0 + 12m = -3 + 15
12m = -3 + 15

Combine like terms: -3 + 15 = 12
12m = 12

Divide each side by '12'.
m = 1

Simplifying
m = 1

See similar equations:

| 3x-0.4=1.4 | | Y+28=x+5 | | 8(x+3)-3x=2(x+12)+3x | | B+ax=2x | | -7v-19=6(1+3v) | | -5(x+3)+8=-7 | | 36w=648 | | 0.4(-5)+6.1= | | 6u^2+u-6=0 | | -2(t-2)+7t=9T-3 | | 3x+7+6x=106 | | -3(y-2)=-2y-1 | | ln(x+1)+ln(3)=ln(2x) | | x-15=4y | | 5.25n=46.50 | | 5*(12-3)=5*e | | 15n=5.25 | | 6a+3+2a=19 | | 8y-16=8y+-16 | | 8=2(4j+1)-5j | | 5(6x+2)-8=30x+2 | | 5(y+9)=-2y-4 | | b=75 | | 9+8=-20 | | -6y+5=16 | | 8x+18=8x-2 | | a^2+ab-72b^2=0 | | 2(v-4)-8v=28 | | 3(t+8)+4=8(t+2)3 | | 14-x=-38 | | 46.50-15=5.25 | | 13x-4=-43 |

Equations solver categories